Using PowerPoint Media to Increase Class V Elementary School Students' Interest in Learning - Leni, Nurhasanah (Universitas Islam Negeri Raden Intan Lampung, 2024)
The aim of this research is to determine the use of powerpoint media in increasing fifth grade elementary school students' interest in learning . The research method used is classroom action research (PTK). The research design adopts the Kemmis and Taggart model which consists of two cycles, each cycle includes planning, acting, observing , reflecting , in 2 meetings. The subjects of this research were 15 fifth grade elementary school students. Data collection through observation and tests. The research results showed that there was an increase in interest in learning after the application of powerpoint media in science subjects as evidenced by the pre-cycle obtaining an average score of 53.46, the number of students who completed was 4 students with a percentage of 13.2%. In the cycle I achieved an average score of 68,7 students completed with a percentage of 46.66 %. In cycle II achieved an average score of 84.33, all students completed with a percentage of 100%. It can be concluded that the use of Powerpoint learning media can increase the learning interest of fifth grade elementary school students